A Network Meta-Analysis of Surgical Treatment in Patients With Early Breast Cancer. (11th June 2019) - Gui, Yu; Liu, Xunzhou; Chen, Xianchun; Yang, Xi; Li, Shichao; Pan, Qingwen; Luo, Xiangdong; Chen, Li
Abstract: Background: In early breast cancer treatment, the preferred surgical regimen remains a topic of controversy, and conventional pairwise meta-analysis cannot provide a hierarchy based on clinical trial evidence. Therefore, a network meta-analysis was performed both for direct and indirect comparisons and to assess the survival outcomes of surgical regimens. Methods: Randomized clinical trials comparing different surgical regimens for the treatment of early breast cancer were identified. Overall survival (OS) and disease-free-survival (DFS) were analyzed using random-effects network meta-analysis on the hazard ratio (HR) scale and calculated as combined HRs and 95% confidence intervals (CIs). All statistical tests were two-sided. Results: The network meta-analysis compared 11 different surgical regimens that consisted of 13 and 17 direct comparisons between strategies for OS (34 trials; n = 23 587 patients) and DFS (32 trials; n = 22 552 patients), respectively. The values of surface under the cumulative ranking for OS and DFS after mastectomy (M)+radiotherapy (RT) were observed to be the largest. Breast-conserving surgery (BCS)+axillary node sampling+RT almost achieved the threshold for inferiority compared with the other surgical treatment arms and was statistically significantly associated with worse OS (HR = 0.51, 95% CI = 0.24 to 0.94; HR = 0.48, 95% CI = 0.22 to 0.92; HR = 0.51, 95% CI = 0.23 to 0.96). No statistically significant difference between BCS+sentinel lymph node biopsy (SLNB)+RT vs BCS+SLNB+intraoperative RT was observed in carrying out network meta-analysis (HR = 0.95, 95% CI = 0.64 to 1.36). Conclusions: M+RT is safer than other surgical regimens for the treatment of early breast cancer patients because of the favorable balance between the survival outcomes. Early breast cancer patients who receive BCS should be given SLNB and not axillary node sampling. Intraoperative RT is no better than postoperative RT in patients who receive SLNB.